Faktor yang Memengaruhi Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Denpasar Timur - Adhimatra, A.A. Gede Wisnu; Noviari, Naniek (E-Jurnal Akuntansi, 2018)
The purpose of this study was to determine the effect of the financial condition of the taxpayer, the quality of service of the tax authorities, and taxation sanctions on individual taxpayer compliance in the East Denpasar Primary Tax Office. The population in this study were all private taxpayers who were registered and effective in 2016 at the East Denpasar Primary Tax Office. The sample in this study was obtained based on the calculation of sample determination using the Slovin formula, then the number of samples used in this study were as many as 100 samples of WPOP registered as Individual Taxpayers in East Denpasar Tax Office. The data analysis technique used is multiple linear regression analysis. The results showed that the taxpayer's financial condition, the quality of service of the tax authorities, and taxation sanctions had a positive effect on WPOP compliance registered in the East Denpasar Primary KPP. This means that if the taxpayer's financial condition, the service quality of the tax authorities, and tax sanctions on the East Denpasar Primary Tax Service Office are getting better, it will further increase the taxpayer's compliance in paying taxes at the East Denpasar Primary Tax Office. Keywords : financial condition, service quality of tax authorities, tax sanctions, WPOP compliance.